Analysis of biology teacher candidates' science process skills in vertebrate zoology courses - Murtini, Iin; Mustofa, Ali; Cintamulya, Imas (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2023)
Science Process Skills (SPS) need to be developed to improve teacher quality in teaching. The existence of the Covid-19 pandemic caused Biology teachers to be unable to carry out practicums so the SPS were helpless. This study aims to analyze the science process skills of biology teacher candidates in vertebrate zoology courses. The research method used is descriptive quantitative through survey techniques. This research was conducted at the PGRI Ronggolawe University and involved 21 participants. This study uses an instrument in the form of an observation sheet to measure scientific process skills. The SPS indicators that are measured are the skills of observing, measuring, compiling tables, and obtaining and processing data. The data obtained is then interpreted into very high, high, low, and very low categories. The percentage of students in each category is then calculated as a map of their science process skills through analysis of quantitative descriptive data. The results showed that 65.5% of prospective biology teachers had SPS scores that were in the very high, high, low, and very low categories. 7.5% has an SPS value which is included in the very low category. In general, biology teacher candidates tend to have very high levels of competency in performing science process skills.